2015
DOI: 10.2174/1874091x01509010015
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and In-silico Studies on Pectin Methylesterase from G9 Variety of Musa acuminata for Delayed Ripening

Abstract: Ripening of fruit is a very important process but in some fruits early ripening leads to a great damage during long distance transportation. There are various biochemical changes taking place during the phase of ripening of fruit such as changes in respiration, aroma, flavor, ethylene production and activity of cell wall degrading enzymes. Some important cell wall degrading enzymes are Polygalacturonase (PG), Pectin methylesterase (PME), Pectin lyase, RGase. PME is known to act as a cell wall hydrolyzing enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The GA content was determined according to Blumenkrantz and Asboe-Hansen (1973) and Verma et al (2014). All CDTA and KOH fractions were analysed for their GA content by m-hydroxydiphenyl method, using GA as a standard ( Figure S2).…”
Section: Determination Of Gamentioning
confidence: 99%
“…The GA content was determined according to Blumenkrantz and Asboe-Hansen (1973) and Verma et al (2014). All CDTA and KOH fractions were analysed for their GA content by m-hydroxydiphenyl method, using GA as a standard ( Figure S2).…”
Section: Determination Of Gamentioning
confidence: 99%
“…PME provides the hydrolysis substrate for polygalacturonase (PG), and functions synergistically with the PG enzyme to soften fruit [ 4 ]. Previous studies have found that PME activity significantly increased associated with the ripening and softening process of various fruits, including banana, mango, strawberry, and kiwi fruit [ 5 , 6 , 7 , 8 ]. During tomato fruit ripening, lower PME activity was associated with an increased content of methylesterification of pectin, a decreased level of total and chelator soluble polyuronides in cell walls, as well as a more soluble solids contain.…”
Section: Introductionmentioning
confidence: 99%